BOOK REVIEW: NEETA INAMDAR, PRIYA VIJAYKUMAR POOJARY, AND PRAVEEN SHETTY, CONTOURS OF INDIA-EU ENGAGEMENTS: MULTIPLICITY OF EXPERIENCES, MANIPAL: MANIPAL UNIVERSAL PRESS, 2021, 451 PP. - BONTEA, George Horațiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2023)
India is becoming a major player on the international stage, with a very ambitious political agenda and ambitious plans for changing the course of world affairs. Its significance increased due to its relationships with other key players in the international arena as well as the acknowledgment of its impact on current international relations, not just because it was economically relevant. Thus, as a result, the European Union was one of the first to deepen and widen its collaboration with India since 2000, with the beginning of a series of summits between India and the EU. The book "Contours of India-EU Engagement: Multiplicity of Experiences" offers a thorough examination of the interactions between the two key players, with a focus on their advancements in politics, education, and culture. Even while the economic sector, as in the case of the Broad-Based Trade and Investment Agreement (BTIA), continues to be the most difficult area of negotiation, this work provides us with an insightful look at how India and the European Union are forging an ongoing partnership. This research project of the Manipal Academy of Higher Education, edited by Neeta Inamdar, Priya Vijaykumar Poojary, and Praveen Shetty, brings together 19 articles written by various scholars focusing on the three main points presented at the beginning of this paragraph: the advancement in important political, educational, and cultural areas between India and the EU.